Effects of energy and protein levels on egg quality and performance of laying hens at early second production cycle - Junqueira, O. M.; de Laurentiz, A. C.; da Silva Filardi, R.; Rodrigues, E. A.; Casartelli, E. M. (Poultry Science Assoc Inc, 2006)
One hundred sixty-two commercial 70-wk-old ISA Brown laying hens, previously subjected to induced molting by feed restriction, were distributed in a completely randomized design with 3 x 3 factorial arrangement (i.e., 3 metabolizable energy levels: 2,850; 2,950, and 3,050 kcal of ME/kg) and 3 protein levels (16, 18, and 20% CP), which totaled 9 treatments with 3 replicates of 6 birds each. Experimental diets were offered to birds after the feed restriction period. Performance and egg quality parameters were evaluated in 14-d intervals from the 4th to 12th weeks after forced molting for a total of 4 evaluation periods. Increases in dietary energy and protein levels did not improve performance or egg quality. The levels of 2,850 kcal of ME and 16% protein were sufficient for laying hens starting the second production cycle without decreasing their performance or egg quality.
Keywords: egg quality; energy; forced molting; performance; protein; semiheavy hen